“That’s something for the vice-minister, no less”: A Korean Fairytale in the State Puppet Theatre in Gdańsk - Joanna Stacewicz-Podlipska (Pamiętnik Teatralny)
This article discusses the circumstances of the staging of the play Arirang in a Polish puppet theatre. This dramatised Korean fairy tale was based on short stories by Dr Tonchu Ru, a Korean living in the Polish People’s Republic, whose biography constitutes a separate important thread of the story. The play premiered on 31st October 1953, four months later than originally planned; this was due to the hostilities on the Korean Peninsula, which forced the producers to get involved in ministry-level exchanges and special diplomacy. Affected by the pressure of a centrally controlled message about the war, the staging was part the Polish ‘engaged’ artists response to the armed conflict in a ‘brotherly’ country. In the face of this conflict, the Polish-Korean ‘parallels’ identified for decades gained a new context, and with it a socialist realist costume.